Traumatic vertebral artery dissection presenting with incomplete congruous homonymous quadrantanopia - Matti, Albert I (BioMed Central, 2010)
BACKGROUND: To describe a rare presentation of vertebral artery dissection (VAD) as a small but congruous incomplete homonymous hemianopia demonstrating use of visual field testing in the diagnosis. CASE PRESENTATION: A 30 year old woman had been unwell for 4 months with difficulty focusing, vertigo, dizziness and a feeling of falling to the right. A small but congruous right inferior homonymous quadrantanopia was found on examination leading to further investigation that uncovered a vertebral artery dissection and multiple posterior circulation infarctions including a left occipital stroke matching the field defect. CONCLUSIONS: We describe an atypical case of VAD presenting with a small congruous quadrantanopia. This is a rare but significant condition that predisposes to multiple thromboembolic infarction that may be easily misdiagnosed and a high index of suspicion is required to make the diagnosis.